(untitled) (International Association of Biologicals and Computational Digest, 2022)
. Malaria remains the leading cause of mortality around the world and is the most common disease in Africa and some countries in Asia with the highest number of indigenous cases with Plasmodium falciparum responsible for the majority of the disease burden. Plasmodium has a complex life cycle consisting of multiple stages in two hosts. During the erythrocytic life cycle, it follows one of two developmental fates: terminal sexual differentiation into gametocytes or asexual propagation. Transmission from an infected human host to a susceptible mosquito is done through highly specialized sexual stages gametocytes because they are the only form of malaria parasite that are transmissible to mosquito vector, hence the discovery of new antimalarials with transmission blocking activity remains a key issue in efforts to control malaria and eventually eradicate the disease. In this study the in silico and in vitro gametocidal properties of one of the Sulfonamide drugs Acetazolamide had been checked in order to find new antiplasmodial agent. In vitro cultivation of the RKL-9 (Chloroquine resistant) strain of P. falciparum was continued to develop sexual gametocytic early stages. The drug acetazolamide was screened for gametocidal assay in order to check its transmission blocking activity by targeting early sexual stages of the parasites. Three Plasmodium falciparum proteins Pfg27, Pfs230 and PUF1were selected for molecular docking with the acetazolamide as ligand. HEX 8.0.0 server was used as docking tool and the results obtained were analysed in Discovery studio visualizer. Our findings of in vitro studies revealed that the selected drug acetazolamide possess promising gametocidal activity with IC50 = 4.812µg/ml. Hence the study can be used further for drug formulations as antimalarials targeting Gametocytic stages. Based on the in silico analysis the good binding scores -196.76, -173.87 and -193.29 (Kcal/mol) were obtained for all three selected Plasmodium falciparum proteins Pfg27, Pfs230 and PUF1 with the ligand acetazolamide respectively. Thus the docking energy results of in silico studies also supported our in vitro results that the acetazolamide can be used as an antiplasmodial drug against the gametocytes. Further studies for the mechanism of action of the acetazolamide as a gametocidal agent can be done for preventing the transmission of malaria.